Acoustic Properties of Collagenous Matrices of Xenogenic Origin for Tympanic Membrane Reconstruction. Issue 6 (July 2016) - Schwarz, David; Pazen, David; Gosz, Kamill; Schwarz, Silke; Nünning, Maike; Gostian, Antoniu-Oreste; Koerber, Ludwig; Breiter, Roman; Rotter, Nicole; Beutner, Dirk
Abstract : Hypothesis: The acoustic properties of scaffolds made from decellularized extracellular cartilage matrices of porcine origin are comparable to those of the human tympanic membrane. Background: Currently, the reconstruction of tympanic membrane in the context of chronic tympanic membrane defects is mostly performed using autologous fascia or cartilage. Autologous tissue may be associated with lack of graft material in revision patients and requires more invasive and longer operative time. Therefore, other materials are investigated for reconstruction. An increasingly important role could be played by scaffolds from different materials, which are known to induce constructive tissue remodeling. Methods: To analyze the acoustic properties, the vibrations of the scaffolds, cartilage, perichondrium and tympanic membrane were measured by laser scanning doppler vibrometry under different static pressures. Results: The analysis of volume velocities serves as an indicator for sound transmission. The results of the average volume velocities at atmospheric pressure show a similar frequency response of the tympanic membrane and the scaffolds with a peak at about 800 Hz. After changing the artificial ear-canal pressure from atmospheric pressure to negative pressure (−100, −200, and −300 daPa) the vibration characteristics of the different membranes remain fairly constant, whereas the results of the perichondrium show a decrease after changing the pressure into the negative range in the frequencies 1 to 3 kHz. Conclusion: The present study showed that the vibration characteristics of the scaffolds under atmospheric and negative pressure can be interpreted as similar to those of thin cartilage (<0.5 mm) and human tympanic membranes. However, in relation to the behavior of these scaffolds made from decellularized extracellular cartilage matrices in vivo, further investigations should be carried out.